The Rights to Religious Freedom and Beliefs: Development, Legal Foundations, and Recent Trends in Austria - Rees, Wilhelm (Ecumeny and law, 2016)
In Austria, there is a variety of churches and religious communities. By recognizing them, the Austrian State gives some of them a special significance. In recent years, the issue of religious freedom has gathered momentum in the aspect of individual freedom of religion as well as the corporate religious freedom, that is, the rights of religious ideological associations. The essay shows the development of the fundamental right toreligious freedom and the legal foundations thereof in Austria. It throws light on theproblem of recognition of churches and religious communities and issues of the individualand corporate freedom of religion, such as affixing crosses and religious education inpublic schools, church bell ringing and the limits of religious freedom. Special attentionis directed to issues facing Muslims, such as whether to wear headscarf or not duringclass, circumcision, mosques and the new Islam Act in Austria. Against the backdrop ofthe history and the legal provisions, brand new questions are conspicuous.